2017
DOI: 10.1186/s12967-016-1108-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in rare cell isolation: an optimization and evaluation study

Abstract: BackgroundRare nucleated CD45 negative cells in peripheral blood may be malignant such as circulating tumor cells. Untouched isolation thereof by depletion of normal is favored yet still technological challenging. We optimized and evaluated a novel magnetic bead-based negative selection approach for enhanced enrichment of rare peripheral blood nucleated CD45 negative cells and investigated the problem of rare cell contamination during phlebotomy.MethodsFirstly, the performance of the magnetic cell separation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This reflects the inability to capture all tumour cells, the heterogeneity of captured cells and the limitations in the molecular assessment of a single cell. Currently, technological inadequacies in the "capture and count" strategy, as well as the complexity of single cell analysis, remain limitations [89,94]. As a diagnostic test, CTC measurement is only accurate in ∼50% of NEN [93] (that is, CTC can be detected in only half of the cases of confirmed metastatic NEN).…”
Section: T -Primary Tumourmentioning
confidence: 99%
“…This reflects the inability to capture all tumour cells, the heterogeneity of captured cells and the limitations in the molecular assessment of a single cell. Currently, technological inadequacies in the "capture and count" strategy, as well as the complexity of single cell analysis, remain limitations [89,94]. As a diagnostic test, CTC measurement is only accurate in ∼50% of NEN [93] (that is, CTC can be detected in only half of the cases of confirmed metastatic NEN).…”
Section: T -Primary Tumourmentioning
confidence: 99%
“…Furthermore, mature cells may be discerned between platelet carrying cells with cytoplasm and those having released their content appearing as cytoplasm-free or naked MKC that may still measure 20 µm in size [11,25,26]. Our investigations on CRC relying on negative selection [27] suggest findings of naked MKC in healthy donor peripheral blood, when compared with published imagery and descriptions of morphology (Figure 1). the CD41a marker.…”
Section: Introductionmentioning
confidence: 49%
“…The authors reported the detection of DRAQ5+/CD41+/concanavalinA−/glycophorin A−/CD45−/CD16− cells and suggested those to be circulating MKC. Similar in principle and suited for MKC isolation are other magnetic cell separation platforms relying on negative selection [27,34]. Moreover, circulating cytoplasmic MKC are best isolated from the right atrium or inferior vena cava using a pressure fixation method [21].…”
Section: Megakaryocyte Isolationmentioning
confidence: 99%
“…However, methods for efficient capture of circulating tumor cells (CTC) from blood samples have been recently developed for liquid biopsy. [34][35][36] Adams et al 34 report that pathologically definable, apoptotic and epithelial-mesenchymal transition-like CTC accounted for 17%, 16% and 58% of cells isolated by one such capture method, respectively. Because our HPLC method is able to detect 5% DNA methylation ( Figure S5), 16%-58% of cancer cells in liquid biopsy samples would be detectable using our system.…”
Section: Discussionmentioning
confidence: 99%